Malathion-induced changes in the haematological profile, the immune response, and the oxidative/antioxidant status of Cyprinus carpio carpio: Protective role of propolis - Yonar, Serpil Mise; Ural, Mevlut Sener; Silici, Sibel; Yonar, M. Enis (Academic Press Inc Elsevier Science, 2014)
The present study investigated the potential ameliorative effects of propolis against malathion toxicity in the blood and various tissues of carp. The fish were exposed to sublethal concentrations of malathion (0.5 and 1 mg/L) for 10 days, and propolis (10 mg/kg of fish weight) was simultaneously administered. Blood and tissue (liver, kidney, and gill) samples were collected at the end of the experiment and analysed to determine the haematological profile (red blood cell count, haemoglobin concentration, haematocrit level, and erythrocyte indices: mean corpuscular volume, mean corpuscular haemoglobin, and mean corpuscular haemoglobin concentration), immune response (white blood cell count, oxidative radical production, nitroblue tetrazolium (NBT) activity, total plasma protein and total immunoglobulin levels, and the phagocytic activity), and oxidant/antioxidant status (malondialdehyde and reduced glutathione levels and superoxide dismutase, catalase, and glutathione peroxidase activities) of the fish. The findings of this study demonstrate that malathion has a negative effect on the haematological parameters, immune response, and antioxidant enzyme activities of the fish. However, the administration of propolis ameliorated the malathion-induced toxic effects. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Malathion; Propolis; Haematology; Immunity; Oxidative stress; Carp